REFLEXIVE INFLUENCE OF SOCIO-PSYCHOLOGICAL THEATRE IN PREVENTATIVE-CORRECTIONAL WORK OF SOCIAL WORKER - Levchuk, Iryna (Social work and education, 2019)
Innovative forms of work play an important role in bringing up a personality, one of them is creation and activity of social-psychological theatre, which forms actively social-psychological ideal, presenting it by certain images, with the help of which social-psychological ideas, moral norms, life values transform in personal experience of a human, temperamental gains of his character. Socio-pedagogical theatre (SPT), forum-theatre and playback theatre are effective in social educator’s prevention and correction work. Socio-pedagogical theatre represents effective methods of group correction, developmental and preventive work with teenagers, as aims at interactive group work. Taking in consideration the fact that socio-psychological theatre is one of interactive methods of social worker’s work, we can outline a few objectives which are realized in the process of its organization. Namely: forming and development of communication and interaction skills; active formation of socio-psychological ideal, which reveals itself in certain psychological images with the help of which socio-psychological ideas, moral norms, life values transform into personal experience; development of decentering (ability to overcome self-centering, ability to take into consideration other points of view); development of emotional (sensory) experience; prevention of personal deviations and social problems. The aim of SPT: pupils’ behavior correction from “risk groups”, help teenagers to adopt in society; healthy way skills formation; prevention of offences among pupils; struggle with negative influence in youth environment; active life position formation. We point out that with the help of reflection which accompanies theatrical performance its participant gains effective tools of self-correction of personal behavior stereotypes.